The semantics of regional society and the problem of internal and external dualism in the analysis of Latin America - Gonnet, Juan Pablo (2023)
In this article we analyze the semantics of the "regional society", which has been established as a widely spread assumption to the conceptualization of the social specificity of Latin America. This semantics considers that geographical and spatial limits are significant for the delimitation of social realities. In this way, it allows us to distinguish between internal and external realities, recognizing their simultaneous value for understanding the social dynamics that unfold in the region. Indeed, it is possible to reconstruct the diversity of theorizations about Latin America as alternative ways in which the links between the internal and the external have been conceived. The paper seeks to develop these hypotheses, while advancing in the evaluation of the theoretical and empirical limits of the semantics. We conclude about the need to move towards a non-regionalist concept of society to approach Latin America.